2020
DOI: 10.26714/jps.8.1.2020.59-64
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Students’ Difficulties in Mastering the Concept of Archimedes’ Principle

Abstract: The focus of this study is to determine students' difficulties related to mastering the concept of Archimedes Principles topics. The study used descriptive quantitative method with the subject 35 XIth students. The research instrument was 10 multiple choice questions about Archimedes principle. Although there are improvements, but overall students do not fully understand the concept of the Archimedes principle. Difficulties among students are failing to understand that the buoyancy force is the resultant force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Several studies also show that students still lack an understanding of buoyancy. Students suppose that the direction of lifting force isn't upward [23]. There are students who argue that the direction of Archimedes is the same as hydrostatic pressure in all directions [24].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also show that students still lack an understanding of buoyancy. Students suppose that the direction of lifting force isn't upward [23]. There are students who argue that the direction of Archimedes is the same as hydrostatic pressure in all directions [24].…”
Section: Resultsmentioning
confidence: 99%
“…Many students did not grasp that the buoyant force is the resultant force of the fluid pressure. Diyana et al showed that students can calculate the magnitude of the buoyant force but fail to understand that the buoyant force is the result of the fluid pressure [3]. Understanding this concept is necessary to understand other concepts in fluid mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Students often do not fully grasp the concept of the Archimedes' principle (Diyana et al, 2020). The Archimedes' principle states that an object immersed in a fluid experiences a buoyant force that is equal in magnitude to the force of gravity on the displaced fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The Archimedes' principle states that an object immersed in a fluid experiences a buoyant force that is equal in magnitude to the force of gravity on the displaced fluid. Students often think that the buoyancy force is the resultant force exerted by fluid pressure on an object, while others still mistakenly believe that the immersed object's Archimedes force is influenced by the depth of the object (Diyana et al, 2020;Loverude et al, 2003). An everyday life example is when a ship is launched in the ocean, it sinks until the weight of the water it displaces is equal to its own weight.…”
Section: Introductionmentioning
confidence: 99%